Pengaruh Artificial Intelligence dan Kecerdasan Emosional terhadap Perilaku Etis Mahasiswa Akuntansi - Emina, Hezi Mufliha; Serly, Vanica (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to determine and analyse the effect of artificial intelligence and emotional intelligence on the ethical behaviour of accounting students. This type of research is quantitative research in the form of causal. The research population was all accounting students at the Faculty of Economics and Business, Padang State University. Sample selection using purposive sampling method. The research sample was 196 active accounting students. The data analysis technique in this study is to use the structural equation model partial least square. Based on hypothesis testing, it can be concluded that the artificial intelligence variable has a positive and significant effect on ethical behaviour. Any increase in the use of artificial intelligence will increase ethical behaviour. Emotional intelligence variables have a positive and significant effect on ethical behaviour. Any increase in emotional intelligence will increase ethical behaviour. The overall effect of artificial intelligence and emotional intelligence variables on ethical behaviour is 78.2% while the remaining amount is influenced by other variables that are outside the research model.